2013
DOI: 10.1002/jgra.50529
|View full text |Cite
|
Sign up to set email alerts
|

Saturn chorus intensity variations

Abstract: [1] Whistler mode chorus plasma wave emissions have been observed at Saturn near the magnetic equator and the source region. During crossings of the magnetic equator along nearly constant L shells, the Cassini Radio and Plasma Wave Science Investigation often observes a local decrease in whistler mode intensity and bandwidth closest to the magnetic equator, where linear growth appears to dominate, with nonlinear structures appearing at higher latitudes and higher frequencies. We investigate linear growth rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…It is possible that there may still be an external driver that modulates the wave excitation, which has not been identified or observed yet, or that the periodicity of the MS waves arises due to an internal instability, analogous to what has been suggested for whistler mode chorus waves [e.g., Bespalov et al , ; Trakhtengerts , ]. The observation of zipper‐like MS waves exhibits additional complexity but may provide a new clue in understanding the causative mechanism of the modulation, which is important since periodic wave structures have been observed in a variety of waves [ Fu et al ., ], including chorus [e.g., Hayosh et al , ; Němec et al , ; Manninen et al , ] and EMIC waves [e.g., Pickett et al , ; Grison et al , ; Sakaguchi et al , ], and they have been observed at other magnetized planets as well [e.g., Menietti et al, ]. Periodic emissions appear to be a universal plasma physical process and are still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that there may still be an external driver that modulates the wave excitation, which has not been identified or observed yet, or that the periodicity of the MS waves arises due to an internal instability, analogous to what has been suggested for whistler mode chorus waves [e.g., Bespalov et al , ; Trakhtengerts , ]. The observation of zipper‐like MS waves exhibits additional complexity but may provide a new clue in understanding the causative mechanism of the modulation, which is important since periodic wave structures have been observed in a variety of waves [ Fu et al ., ], including chorus [e.g., Hayosh et al , ; Němec et al , ; Manninen et al , ] and EMIC waves [e.g., Pickett et al , ; Grison et al , ; Sakaguchi et al , ], and they have been observed at other magnetized planets as well [e.g., Menietti et al, ]. Periodic emissions appear to be a universal plasma physical process and are still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…The precipitating electron energy spectrum can also be affected by the efficiency of pitch angle scattering in the magnetosphere. Whistler‐mode chorus waves have been detected by previous observations and can resonate with electrons with energies from a few 100 s eV to a few keV [ Hospodarsky et al ., ; Menietti et al ., ]. Whistler‐mode hiss waves are associated with the FA electron beam with energy of a few 100 eV [e.g., Kopf et al ., ; Gurnett et al ., ].…”
Section: Discussion: Use Of the Auroral Emission As A Diagnosis Of Thmentioning
confidence: 99%
“…A source of temperature anisotropy near the Enceladus torus may be damping of ion cyclotron waves which have been identified and studied by many researchers [cf. Leisner et al, 2006;Menietti et al, 2013]. The narrow size of the source location may be due to the steep gradient in the density in this inner region of the Saturn magnetosphere.…”
Section: Discussionmentioning
confidence: 99%